The Social Rate of Return on Infrastructure Investments - Canning, David (World Bank, Washington, DC, 2014)
The authors estimate social rates of return to electricity-generating capacity and paved roads, relative to the return on general capital, by examining the effect on aggregate output and comparing that effect with the costs of construction. They find that both types of infrastructure capital are highly complementary with other physical capital and human capital, but have rapidly diminishing returns if increased in isolation. The complementarities on the one hand, and diminishing returns on the other, point to the existence of an optimal mix of capital inputs, making it very easy for a country to have too much - or too little - infrastructure. For policy purposes, the authors compare the rate of return for investing in infrastructure with the estimated rate of return to capital. The strong complementarity between physical and human capital, and the lower prices of investment goods in industrial economies, means that the rate of return to capital as a whole is just as high in rich countries as in the poorest countries but is highest in the middle-income (per capita) countries. In most countries the rates of return to both electricity-generating capacity and paved roads are on a par with, or lower than, rates of return on other forms of capital. But in a few countries there is evidence of acute shortages of electricity-generating capacity and paved roads and, therefore, excess returns to infrastructure investment. Excess returns are evidence of suboptimal investment that, in the case of paved roads, appears to follow a period of sustained economic growth during which road-building stocks have lagged behind investments in other types of capital. This effect is accentuated by the fact that the relative costs of road construction are lower in middle-income countries than in poorer and richer countries. As a rule, a tendency to infrastructure shortages - signaled by higher social rates of return to paved roads or electricity-generating capacity than to other forms of capital - is symptomatic of certain income classes of developing countries: electricity capacity in the poorest, paved roads in the middle-income group. To the extent that such high rates of return are not detected by microeconomic cost-benefit analysis, they suggest macroeconomic externalities associated with infrastructure.